Improving Filtration Efficacy of Medical Face Masks - Ilpo Kulmala; Kimmo Heinonen; Satu Salo (Aerosol and Air Quality Research)
Abstract We built a simple unipolar positive corona charger and tested it with five different medical face masks. Charging the particles significantly enhanced the filtration efficiencies of all of the masks in terms of the submicron fraction, with an average increase of from 58 to 93% for 0.3 µm particles. Simultaneously, the pressure drop remained practically the same, showing the high potential in using electret media. However, the corona discharge generated ozone, which is an issue that must be addressed. These results contribute to the development of effective solutions against airborne threats.